Spectacle Independence and Quality of Vision After Bilateral Implantation of a Trifocal Intraocular Lens - Shatz, Andrew C; Potvin, Richard (Clinical ophthalmology (Auckland, N.Z.), 2021)
To evaluate the patient-reported spectacle independence and quality of vision for patients who were bilaterally implanted with a trifocal intraocular lens (IOL). Single site, prospective, single-arm study. Subjects presenting for cataract surgery who had an interest in reducing their dependence on glasses at multiple distances were enrolled. Subjects were bilaterally implanted with a trifocal IOL and followed for 3 months post-surgery. A spectacle independence questionnaire and a quality of vision questionnaire were administered at the 3-month visit. The binocular visual acuity at distance (4 m), intermediate (60 cm) and near (40 cm) was also measured in the uncorrected and distance-corrected state. All but one subject reported no need for glasses for distance and intermediate work, and most (25/29) reported no need for glasses for near work. Almost all subjects reported never wearing glasses or wearing them only a little, and being able to function without glasses at any distance all or most of the time. Ninety percent of subjects (26/29) reported being completely or mostly satisfied with their vision overall, without the use of glasses or contact lenses. The mean binocular visual acuity 1 and 3 months after surgery was better than 0.1 logMAR (20/25) at all test distances in both the uncorrected and distance-corrected states. The reported quality of vision appeared similar to previously reported data for the same IOL. The trifocal IOL provided nearly all subjects with functional vision and spectacle independence for distance, intermediate and near work. It is a viable alternative for patients looking to reduce their overall dependence on spectacles after cataract surgery.